Shale pore characteristics of Shahejie Formation: Implication for pore evolution of shale oil reservoirs in Dongying sag, north China - Shun Zhang (Petroleum Research, 2019)
The pore characteristics of shale reservoirs in the lower submember of Member 3 to upper submember of Member 4 of Shahejie Formation in Dongying sag are analyzed, influences of mineral content and organic matter content on porosity and pore size are also investigated, and through the diagenetic thermal simulation experiment, the main pore evolution is further discussed. The results show that the pore structure of shale reservoirs is complex, the micron-nanometer pores can storage liquid hydrocarbons, and the free-phase crude oil is mainly distributed in intergranular dissolution pores of calcite, recrystallized intergranular pores, intergranular shrinkage fractures of clay mineral which have large pore size. Framework minerals and organic matter content directly influence porosity and pore size of shale reservoirs, relationship between porosity and content of felsic mineral as well as content of organic matter content is linear and positive, while relationship between content of carbonated mineral is negative. At the buried depth from 2500 to 3500 m, concentration of organic acid from hydrocarbon generation and expulsion of organic matter, increasing range of pressure coefficient, are well corresponding to high-porosity intervals; pore formation in shale oil reservoirs are almost controlled by diagenetic evolution of clay minerals; framework storage spaces formed by carbonate grain crystals as well as intergranular and intergranular dissolution pores of carbonate increases porosity of shale oil reservoirs; local increase of porosity at the depth of 3500–3800 m is mainly caused by coupling of hydrocarbon-generating overpressure and dissolution, and size, distribution and connectivity of pores are enhanced obviously. Keywords: Shale oil, Pore and fracture, Diagenesis, Clay mineral transformation, Dissolution, Recrystallization, Hydrocarbon-generation and acid expulsion, Paleogene, Dongying sag